Travel Motivations of Domestic Film Tourists to the Hengdian World Studios: Serendipity, Traverse, and Mimicry. Issue 3 (1st October 2016) - Meng, Yutong; Tung, Vincent Wing Sun
ABSTRACT: While past studies have sought to understand the travel motivations of international film tourists, more attention can be paid to examine the motivations from domestic visitors. This distinction is critical as domestic tourists have different travel experiences, familiarity, and cultural proximity with their country than international tourists, which can affect their travel motivations. To address this research gap, this study examines domestic tourists' motivations for visiting the Hengdian World Studios in China via a netnographic approach. Three dimensions were identified, reflecting interpretations from tourists' voices: their desire for serendipitous experiences, to traverse and dream, and to compare the mimicry of Hengdian to real heritage sites in China. This study contributes to the literature from a psychological perspective by analyzing post-trip reflections to infer pre-trip motivations. This study also provides implications for tourism marketers in other emerging countries where some of the world's largest film destinations are being developed.